Haemolysis risk in methylene blue treatment of G6PD-sufficient and G6PD-deficient West-African children with uncomplicated falciparum malaria: a synopsis of four RCTs - Müller, Olaf; Mockenhaupt, Frank Peter; Marks, Bernd; Meissner, Peter; Coulibaly, Boubacar; Kuhnert, Ronny; Buchner, Hannes; Schirmer, Rolf Heiner; Walter-Sack, Ingeborg; Sié, Ali; Mansmann, Ulrich (Pharmacoepidemiology and drug safety, 2013)
Purpose Methylene blue (MB), which was recently tested in a number of clinical malaria studies in Burkina Faso, is currently investigated for its benefit when added to artemisinin-based combination therapy. Together with a number of other antimalarials, MB is on the list of drugs which potentially induce haemolysis in patients with G6PD deficiency. Ruling out safety concerns is of major importance during drug development. Methods A pooled analysis was performed with patient data from four clinical studies conducted in West African children with falciparum malaria between 2003 and 2007. The primary endpoints were haemoglobin levels over time as well as haemolysis in G6PD-deficient (n = 199) and G6PD-sufficient (n = 806) children treated with MB-containing (n = 844) compared to children without MB-containing (n = 161) drug regimens. Results In the chosen model, the haemoglobin time course was significantly influenced by the G6PD genotype and the MB dose. In children with hemi- or homozygous G6PD (A-) deficiency, MB treatment with 15 mg/kg per day was associated with a significant reduction in Hb values which reached a minimum of 8.5 g/dl. Two episodes of haemolysis occurred (out of 1005 children); one in a girl heterozygous for G6PD deficiency and one in a hemizygous boy, both had received MB. Conclusions MB treatment of malaria in Africa is associated with slightly reduced haemoglobin values in children with a full G6PD defect compared to non-G6PD deficient children. This effect appears to be of limited clinical relevance but needs to be monitored. Copyright © 2012 John Wiley & Sons, Ltd.
Published online 7 November 2012
Gesehen am 22.06.2021